Detection and determination of undeclared synthetic caffeine in weight loss formulations using HPLC-DAD and UHPLC-MS/MS - Carine Viana; Gabriela M. Zemolin; Thaís R. Dal Molin; Luciana Gobo; Sandra Maria Ribeiro; Gabriela C. Leal; Gabriela Z. Marcon; Leandro M. de Carvalho (Elsevier, 2018)
Caffeine is present in products marketed for weight loss, with the purpose of increasing thermogenesis and lipid metabolism. The dosage declared by the product manufacturer, or even its presence, is not always correctly described on the label. This work aimed to investigate the undeclared synthetic caffeine in weight loss formulations by a high-performance liquid chromatography with diode array detection (HPLC-DAD) method. From one hundred products purchased through Brazilian e-commerce, seventeen contained caffeine, either naturally or synthetically added to formulation. The caffeine-containing samples were confirmed by an ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method, and adulteration was clearly proven in five products. The content highest caffeine contained 448.8 mg per dose. Other irregularities were also found; nevertheless, the most serious was the addition of synthetic drugs without asking the consumers. Additional drugs expose the consumer to more possible side-effects as well as deleterious drug interactions. Intentional adulteration with any unlabeled substance is typically motivated by a desire to increase or alter the claimed effect of the marketed product to gain a commercial advantage. Keywords: Undeclared synthetic caffeine, Weight loss formulations, HPLC-DAD, UHPLC-MS/MS